Odpowiedzi

2010-01-27T17:20:18+01:00
1. (x+y/3)+(y/5)=-2
2. (2x-y/3)-(3x/4)=3/2

1. x+y/3+y/5=-2 |*30
2. 2x-y/3-3x/4=3/2 |*12

1. 30x+10y+6y=-60
30x+16y=-60 |:(-2)
2. 24x-4y-9x=18
15x-4y=18
1. -15x-8y=30
2. 15x-4y=18
-12y=48
-y=4
y=-4

2. 15x-4*(-4)=18
15x+16=18
15x=2
x=2/15

x=2/15
y=-4
Najlepsza Odpowiedź!
2010-01-27T17:27:01+01:00
(x+y/3)+(y/5)=-2 /×5
(2x-y/3)-(3x/4)=³/₂ /×4

(5 (x+y)/3)+y=-10/×3
(4(2x-y)/3)-3x=6/×3

5x+5y+3y=-30
8x-4y-9x=18

5x+5y+3y=-30
-x-4y=18 /×2

5x+8y=-30
-2x-8y=36
3x=6/÷3
x=2

5×2+8y=-30
10+8y=-30
8y= -30 - 10
8y=-40/÷8
y=-5

x=2
y=-5

Powinno być dobrze :)